Evaluating Graduate Capabilities and Workplace Relevance Through Tracer Studies: Evidence from a Master’s Program in Islamic Education at Institut Agama Islam Negeri Lhokseumawe - Nurhayati Nurhayati; Syahrizal Syahrizal; Samsul Bahri; Sarsembayev Ruslan; Nor Asmahan Binti Abdul Kadir (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Tracer studies are essential for evaluating the relevance of higher education programs to the workforce and understanding the capabilities of alumni. The PAI Postgraduate Program at IAIN Lhokseumawe has yet to track graduate outcomes and stakeholder perceptions systematically. This study aims to examine the employment status, workplace relevance, and competency capabilities of graduates from the PAI Postgraduate Program, as well as stakeholder responses to their performance. A mixed-methods sequential explanatory design was employed. Quantitative data were collected through questionnaires from 116 graduates of the 2018–2021 cohorts, while qualitative data were obtained through interviews with graduates and stakeholders. Data analysis included descriptive statistics, cross-tabulation, and thematic analysis for qualitative insights. The findings indicate that 92.5% of graduates are employed, with 93.7% working in fields relevant to their education. Key competencies such as integrity, professionalism, IT literacy, communication, teamwork, and self-development were rated excellent by both graduates and stakeholders. Nevertheless, foreign language proficiency (English and Arabic) emerged as an area for improvement. Alumni also highlighted the importance of networking and continuous professional development to enhance employability. The PAI Postgraduate Program effectively prepares graduates with competencies aligned to workplace demands, achieving high employment rates and stakeholder satisfaction. However, targeted improvements in foreign language skills and professional networking are recommended to further enhance graduate competitiveness. These results provide practical guidance for curriculum development and program evaluation to maintain relevance and quality.